NaOH Molarity Effect on Mechanical and Hydrochloric Acid Resistance of Geopolymer Mortar Based on Slag - Mahmoud Ziada; Zahraa Mohammed Kamil Al-Mayali (Journal of Sustainable Construction Materials and Technologies, 2025)
The present research investigates the influence of different sodium hydroxide (NaOH) molarities on the mechanical characteristics and hydrochloric acid (HCl) resistance of geopolymer grouts manufactured from ground granulated blast furnace slag (GGBS). Geopolymer mortars have attracted interest as sustainable substitutes for traditional cementitious materials due to their advantageous environmental effects and enhanced durability features. This study involved the fabrication of geopolymer mortar specimens by altering the NaOH molarity (M) from 6 M to 14 M. The mechanical and physical qualities were assessed using compressive strength, capillary water absorption, flexural strength, slump flow, and ultrasonic pulse velocity (UPV) tests. Subsequently, the geopolymer mortar specimens with various molarities were exposed to 5% HCl to evaluate the HCl resistance of these specimens by subjecting the specimens to a 5% HCl solution for 28 days. Compressive strength, microstructural analysis, flexural strength, UPV, and mass changes tests were also conducted after 14 and 28 days of exposure to HCl. The results indicate that the molarity of NaOH substantially affects both mechanical strength and resistance to acid degradation. After 28 days of HCl exposure, an increase of 59.63% was observed in the compressive strength of the 10 M containing sample compared to the 6 M containing sample, while this increase decreased to 43.84% in the 14 M sample. This work highlights the essential significance of NaOH molarity in optimizing geopolymer formulations for use in harsh settings, providing insights into the equilibrium between strength enhancement and durability.